Oral Candidiasis pada Pasien dengan Riwayat Radioterapi sebagai Perawatan Kanker Prostate: Laporan Kasus: Oral Candidiasis in Patient with a History of Radiotherapy as a Treatment for Prostate Cancer: A Case Report - Nabila, Haidy; Wijayanti, Husni; Oktadewi, Fitri; Silva, Ghea (Fakultas Kedokteran Gigi IIK Bhakti Wiyata, Kediri., 2025)
Background: Radiotherapy is one of the treatments given to cancer patients. The effects of radiotherapy can affect systemic conditions and the oral cavity. One of the effects that occurs in the oral cavity is the emergence of oral candidiasis infection. Objective: Describes the clinical findings and management of oral candidiasis in prostate cancer patients with a history of radiotherapy.. Case: A 72-year-old male patient complained of weakness, dizziness, bone pain, body aches, and muscle aches. The patient has a history of prostate cancer, bone metastases and routinely undergoes examinations at Moewardi Hospital. History of chemotherapy 6 times, and 10 times of light radioterapy. Intraoral examination showed a primary lesion in the form of a unilateral irregular white plaque on the lateral tongue in white with a soft consistency. The patient had difficulty opening his mouth. Case management: Systemic therapy in the form of infusion. NaCl 3% 500 ml, Inj Ceftriaxone 2x1 gr, Inj Ketorolac 2x30 mg, Po. Elkana 1x1. Conclusion: Oral candidiasis is one of the oral cavity infections caused by Candida albicans fungal infection. Conditions in patients with a history of radiotherapy can be a predisposing factor for the emergence of this infection. First-line topical antifungal therapy in the form of nystatin can relieve lesions along with information communication and education.